Diagnostic value of a single β-hCG test in predicting reproductive outcomes in women undergoing cleavage embryo transfer: a retrospective analysis from a single center - Yuchao Zhang; Zhen Li; Bingnan Ren; Wenbin Wu; Yanli Liu; Xingling Wang; Yichun Guan; Liting Jia (BMC, 2022)
Plain Language Summary To investigate the association between β-hCG and reproductive and obstetrical outcomes in women with cleavage ET and to establish different β-hCG cutoff values for the prediction of reproductive outcomes, this study retrospectively included 6909 infertile women who were divided into different groups based on the number and quality of transferred embryos, age, and transfer protocols. The cutoff values of β-hCG for predicting the presence/absence of pregnancy, biochemical pregnancy/clinical pregnancy, presence/absence of adverse pregnancy outcomes, singleton/twin live birth in the cleavage groups were 89.6, 241.1, 585.9, and 981.1 mIU/L, respectively. Biochemical pregnancy rates and adverse pregnancy outcome rates decreased significantly in the higher β-hCG groups. In conclusion, the interpretation of β-hCG levels must consider the number and quality of embryos and transfer protocols. When β-hCG was tested on a fixed day post-ET, different cutoff values were required for the prediction of early clinical outcomes.